Learning for Children with Special Needs of Dyscalculia - Azhari, Budi; Yacoeb, Muhammad; Irfan, Ade (SCAD Independent, 2020)
This study aimed to develop mathematics learning tools to help children with special needs of dyscalculia in elementary school. The procedural development of the device was through a 4-D model consisting of four phases; defining, designing, developing, and disseminating. However, based on the research objectives, this development was limited only to the development stage (develop), which is to the learning device testing activities. So the development of learning tools in this study consisted of three main stages, namely: defining, designing, and development. The results of this study illustrated that learning devices for children with dyscalculia learning disorders could help children more easily deal with learning difficulties. Specifically, it is on the topic of sequencing numbers, addition, and subtraction of integers.